(untitled) (KASBIT Business Journal, 2022)
As employees’ commitment is an integral part of human resource management and crucial for every organization to flourish and succeed, there is much research on this aspect. However, this research finds and determines the factors that play an essential role in identifying employees’ commitment to university teachers. In this study, five independent variables were examined to determine their effect on the employees’ commitment. The predictors were work motivation, procedural justice, training opportunities, work environment, and career development. To determine the significant relationship between the independent and dependent variables, Pearson’s Correlation has been run. Also, multiple regression analysis has been conducted to find the impact of predictors on employees’ commitment. Results show that procedural justice and career development have a significant relationship with employees’ commitment. In contrast, the other three independent variables – work motivation, training opportunities, and work environment have an insignificant relationship with employees’ commitment. Conclusions formulated from this study are that procedural justice and career development are the two significant predictors of employee commitment of universities teachers. To strengthen the employees’ commitment to university teachers, employers must implement these practices in the universities.